Determination of in vitro and in vivo protective effects of Ghrelin against oxidative stress: Experimental Study - Mahdi Nazoury, Seyed-Mostafa Hosseini-Zijoud, Mohammad Soukhtanloo, Baratali Mashkani, Seyed Isaac Hashemy (Journal of Applied Pharmaceutical Science, 2014)
Antioxidant properties of ghrelin have been recently reported in animal models and cell culture experiments. This study was set to examine the possible in vitro and in vivo anti-oxidative effects of ghrelin in rat and HepG2 cell culture. In this study, thirty six male Wistar Rats were randomly allocated into six experimental groups of six; Intraperitoneally, group 1 (Control) received 1 ml PBS, group 2 received 0.1 mM/kg tert-Butylhydroperoxide (t-BOOH), groups 3 and 4 received 0.1 mM/kg t-BOOH and then received 10 and 50 µg/kg ghrelin, respectively. Groups 5 and 6 received 10 and 50 µg/kg ghrelin, respectively. Rats were anesthetized 24 h after last injection and blood samples were taken by cardiac puncture. Carbonylated proteins, nitric oxide (NO) and total antioxidant capacity (TAC) levels were measured in sera. HepG2 cells were plateaued at a density of 1.5 x 105 per well in eight plates. After treatment with ghrelin (0, 10, 25 and 50 nM) for 30 min, cells were treated with T-BOOH (100 or 200 µM) for 24 h to analyze cell proliferation by MTT assay at 570 nm. Evidence of oxidative stress including increased carbonylated proteins and NO levels and decreased TAC level were observed after t-BOOH injection. In rats with oxidative stress, subsequent treatment with ghrelin decreased NO and carbonylated proteins level and increased TAC level. The cell viability was decreased after t-BOOH treatment in dose dependent manner; in contrast, ghrelin in all used concentrations caused an elevation in cell viability after 24 h incubation time. These data taken together indicate that ghrelin reduces oxidative stress, but its exact mechanism is yet to be investigated.
Keywords: Ghrelin, oxidative stress, ROS, HepG2, Rat.